Energy Efficient Homes: Landscaping - Terry B. DelValle; Joan Bradshaw; Barbra Larson; Kathleen C. Ruppert (EDIS, 2008)
FCS-3281, a 9-page fact sheet by Terry B. DelValle, Joan Bradshaw, Barbra Larson, and Kathleen C. Ruppert, describes the important role landscaping plays in modifying the home environment, how to plan, cultivate, and maintain landscapes that are energy efficient, provide wind protection, and contribute active or passive cooling. Includes references. One of an Energy Efficient Homes series. Published by the UF Department of Family Youth and Community Sciences, June 2008.